PENGEMBANGAN BAHAN AJAR BERBASIS MULTIMEDIA INTERAKTIF PADA MATA KULIAH PENDIDIKAN SENI MUSIK DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR STKIP PGRI LUBUKLINGGAU - Abi Karoma Batubara; Dedy Firduansyah (FIP Unimed, 2020)
The aimed of this research was to create a teaching materal product based on multimedia interactive at PGSD Study program of STKIP PGRI Lubuklinggau. The mothod of this research was research and development by Rowntree model. The result of language validation gotten score avarage 3,25 that have meaning valid. The Material validation gotten score avarage 4,62 that has meaning valid. The media validation gotten score avarage 4,24 that has meaning valid. In the small group test, researcher got the score avarage 81,11. It showed the result of developing material was valid and practice.Keyword : Development, Material, Multimedia Interactive